2019
DOI: 10.1182/blood-2019-126285
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Phase III Double-Blind Study of the Addition of Tocilizumab Vs. Placebo to Cyclosporin/Methotrexate Gvhd Prophylaxis after HLA-Matched Allogeneic Stem Cell Transplantation

Abstract: Background: IL-6 mediates graft-vs.-host disease (GVHD) in experimental models of allogeneic stem cell transplantation. The addition of a humanized anti-IL-6R mAb (Tocilizumab; TCZ) to standard GVHD prophylaxis has shown in promise in reducing the incidence of acute GVHD in two prospective phase I/II clinical studies. Aims: To determine the efficacy of TCZ in preventing grade II-IV acute GVHD in patients with acute leukaemia or myelodysplasia undertaking 8/8 matched related sibling (MSD) or matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A phase II trial in which patients received busulfan-based conditioning prior to receiving tocilizumab with tacrolimus and methotrexate showed a low incidence of gastrointestinal GVHD (38). Recently, a phase III randomized and double-blinded trial observed a trend toward a reduced overall incidence of grade II-IV GVHD in patients receiving tocilizumab, but no difference in long term survival compared to controls (39).…”
Section: Anti-il-6mentioning
confidence: 99%
“…A phase II trial in which patients received busulfan-based conditioning prior to receiving tocilizumab with tacrolimus and methotrexate showed a low incidence of gastrointestinal GVHD (38). Recently, a phase III randomized and double-blinded trial observed a trend toward a reduced overall incidence of grade II-IV GVHD in patients receiving tocilizumab, but no difference in long term survival compared to controls (39).…”
Section: Anti-il-6mentioning
confidence: 99%
“…It is logical that inhibiting the very movement of effector T-lymphocytes to target organs should better prevent GVHD rather than trying to arrest the widespread inflammation and cytokine cascades which characterize the final common pathway in GVHD pathogenesis. As a testimony to that, when tocilizumab an IL-6 blocker was evaluated, despite promising phase II single-arm data, was not more effective than standard prophylaxis in a phase III RCT ( 71 ). This has in fact been the case with numerous promising prophylactic therapies which perform well in single-arm studies but have not been a home run in well-designed phase III studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, IL-6 blocking agents could prevent aGVHD. In a phase II trial, tocilizumab, a humanized monoclonal antibody against the IL-6 receptor (IL-6R) was found to be promising ( 70 ); however, in a placebo-controlled phase III study from Australia, there was no significant difference in grades II-IV or III-IV aGVHD ( 71 ). This is a salient reminder that given the complex pathophysiology of aGVHD, with crosstalk between myriad cytokines and immune effector cells, targeting multiple cytokine pathways will be required for efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Based on promising phase II data, 79 a placebo-controlled phase III study from Australia was reported, which, however, showed no significant difference in grades II-IV or III-IV aGvHD. 80 This is a salient reminder that, given the complex pathophysiology of aGvHD, with crosstalk between myriad cytokines and immune effector cells, it is possible that targeting multiple cytokine pathways will be required for efficacy.…”
Section: Cytokine Targetingmentioning
confidence: 99%